Symbiotic anti-oxidant, anti-glycation, and anti-inflammatory qualities of a combination of thiamine and niacin protected type-2 diabetic male rats against both macro and micro-vascular complications - Sina Mahdavifard; Hamid Reza Malekzadeh (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Increased nuclear factor (NF-kβ) and carbonyl stress due to decreased glyoxalase-1 activity (Glo-I) contribute significantly to insulin resistance and vascular complications. Therefore, we aimed to study the impact of the combination of thiamine and niacin on hepatic NF-kβ signaling, metabolic profile, and Glo-I activity in male rats with type-2 diabetes (T2DM).Materials and Methods: Forty male rats were divided equally into five groups: control, diabetic, diabetic treated with thiamine (180 mg/l in drinking water), niacin (180 mg/l), and a combination of both. The treated groups received the treatments daily in drinking water for two months. T2DM was induced using a combination of nicotinamide and alloxan. Metabolic profile and renal dysfunction parameters were assessed. Additionally, various glycation, oxidative stress, and inflammatory markers were measured.Results: The treated group with both vitamins showed the lowest blood sugar and insulin resistance indices, cardiovascular indices, renal dysfunction parameters, hepatic NF-kβ expression, oxidative stress, inflammatory and glycation markers, and the highest anti-oxidant and anti-glycation markers, β cell activity, and insulin sensitivity. Thiamine exhibited more anti-inflammatory activity than niacin in diabetic rats, while niacin demonstrated stronger anti-oxidant activity (P<0.001).  Conclusion: The combined use of vitamins had a more beneficial impact on macro and microvascular complications in diabetes than each alone, attributed to their higher anti-oxidant, anti-inflammatory, and anti-glycation characteristics. The vitamins also had a more corrective effect on glucose-lipid metabolism, insulin sensitivity, and renal function through a stronger lowering effect on hepatic NF-kβ expression.